Strategy and organization realizing strategic management - Heracleous, Loizos Th (Cambridge University Press, 2003)
Examining some of the new and emerging issues in strategic management, Loizos Heracleous offers a fresh approach to the established ideas of strategy. Beginning with the historical development of the strategy field, including the influence of industrial organisation and the resource-based view, he develops a new perspective labelled an 'organisational action' view of strategy. This approach is theoretically underlain by organisation theory and takes seriously such issues as the role of agency, the need for a longitudinal focus on process, the complexities of strategy implementation, and organisational facets such as strategic choice, organisational culture, organisational discourses and learning. Combining theoretical subtlety with an applied orientation, Heracleous examines topical areas such as corporate governance, inter-organisational networks, and organising for the future. With original research and extensive surveys of the strategy literature, combined with a strong practical orientation, this book is ideal for MBA students, strategy researchers and the more thoughtful practitioner